Penurunan Berat Timbulan Sampah Buah Jeruk Mandarin (Citrus reticulata) Menggunakan Maggot Black Soldier Fly (Hermatia illucens) Tahun 2021:Studi Awal - Atang Saputra; Muhammad Akmal; Agus Riyanto; Budi Pramono (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Organic waste is an item that is no longer used or discarded by its owner, organic waste can be used or reprocessed into something useful. Organic waste is waste that can experience weathering or decomposition and breaks down into smaller materials. Organic waste at the Kramat Jati Main Market, East Jakarta, is disposed of directly and there is no prior sorting process, so the waste piles up. One of the methods for reducing the weight of waste generation is by using the maggot Black Soldier Fly medium. This study entitled "Reducing the Weight of Waste Generation of mandarin Oranges (Citrus reticulata) Using the maggot Black Soldier Fly (Hermatia illucens) in 2021: Preliminary Study" has the aim of determining the reduction in the weight of waste generation every day for 1 week. This experimental research was carried out within 7 days and used 10 kg of mandarin orange (Citrus reticulata) waste using 1 kg of maggot Black Soldier Fly. One method to reduce the weight of mandarin orange (Citrus reticulata) waste generation is by using the maggot Black Soldier Fly, which later the mandarin orange (Citrus reticulata) waste will be reduced by the maggot Black Soldier Fly by giving 10 kg of mandarin orange (Citrus reticulata) waste.) then calculated the decrease every day for 7 days and the maggot Black Soldier Fly that will be used in this study is approximately 13 days old. Based on the results of the study, it was found that the weight reduction of waste generation before treatment was 10 kg and after decomposition for 7 days resulted in a high decrease, which was obtained as much as 9,450 kg. The remaining waste from decomposition is 550 g of mandarin orange (Citrus reticulata) waste with a percentage of 94.5% decrease.